Literature Review: Hubungan Kadar D-Dimer dengan Tingkat Keparahan Pasien Covid-19: Literature Review: The Relationship of D-Dimer Levels with the Sverity of Covid-19 - Ismi Andina Pertiwi; Tantri Analisawati Sudarsono; Dita Pratiwi Kusuma Wardani; Minto Rahaju (Jurnal Surya Medika (JSM), 2023)
Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) causes Corona Virus Disease-19 (COVID-19). D-dimer is one of the hemostasis tests performed on patients infected with the disease, it is a product of fibrin degradation and a biomarker of platelet disorders. With the development of COVID-19 as a pandemic, D-dimer has become an indicator for prognosis in COVID-19 patients. Based on symptoms, the severity of COVID-19 patients consists of mild, moderate, and severe symptoms. The author conducted a literature review regarding the correlation between D-dimer levels and the severity of COVID-19 patients. Data and theory were taken from ten references from several databases: Google Scholar, PubMed, Semantic Scholar, Science Direct, Garuda, and Neliti. The references taken were from the 2020-2022 range. In all of these references, statistical test results were obtained with a significant value below 0.05, so it can be concluded that there is a correlation between D-dimer levels and the severity of COVID-19. In COVID-19 infections with severe symptoms, immunothrombosis can occur due to hyperinflammatory conditions and cytokine storms. Immunothrombosis occurs as a result of the body's defense against viral infections. Damage to lung tissue in COVID-19 patients triggers a procoagulant response associated with inflammatory cytokines in blood vessel tissue.